Scheduling elective surgeries in a Portuguese hospital using a genetic heuristic - Marques, Inês (2014)
The Portuguese National Health Plan outlines two main guidelines for hospital units: improve the efficient use of the available resources and reduce the waiting list for surgery. The aim of this work is to provide a contribution in the field of operations research to achieve these guidelines. The operating theater is a hospital unit that represents a great proportion of the hospital budget. Furthermore, it is a central service with connections and implications in the service of many other hospital units. Therefore, this work is dedicated to a case study of an elective surgery scheduling problem arising in a Portuguese public hospital. The problem consists of assigning an intervention date, an operating room and a starting time for elective surgeries that remain in the hospital waiting list, thus combining simultaneously advance and allocation scheduling. Two conflicting optimization criteria are independently considered: maximize the surgical suite occupation and maximize the number of surgeries scheduled. Two versions of a single objective genetic heuristic are developed and applied to real data from the studied hospital. The results show that this approach improves the quality of the hospital surgical plans in light of the objectives considered, requiring much fewer resources to construct the surgical plans. Real instances with 508–2306 elective surgeries are successfully solved in less than 240s. These are better results than authors’ previous approaches to the same problem